Impact of salinity on CO2 containment security in highly heterogeneous reservoirs. Issue 1 (8th September 2017) - Al‐Khdheeawi, Emad A.; Vialle, Stephanie; Barifcani, Ahmed; Sarmadivaleh, Mohammad; Zhang, Yihuai; Iglauer, Stefan
Abstract: It is well established that brine salinity can vary substantially in prospective CO2 geo‐storage reservoirs. However, the impact of salinity on containment security has received only little attention. We thus used a compositional reservoir simulation to evaluate the effect of salinity on CO2 plume migration and CO2 trapping capacities in a 3D heterogeneous reservoir. The used heterogeneous reservoir consists of two formations: the bottom part of the reservoir is a fluvial reservoir, and the top part represents a near‐shore environment. Our results clearly indicate that salinity has a significant influence on CO2 migration and the relative amount of mobile, residual, and dissolved CO2 . Lower salinity decreases CO2 mobility and migration distance, and enhances residual and solubility trapping significantly. We thus conclude that brine salinity is an important impact factor in the context of CO2 geo‐storage, and that less saline reservoirs are preferable CO2 sinks due to increased storage capacity and containment security. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd.